Entrance of the Antarala of the Sitaleshwar Temple - Temples of India Project Team (Jio Institute, 2024)
The entrance of the antarala (vestibule or antechamber) of the Sitaleshwar Temple is distinguished by its four pillars that feature carvings that significantly differ from those of the mandapa (pillared hall), a later addition. The decorative patterns and carving style evoke similarities with the artistic style seen in Ajanta paintings. These pillars showcase intricate carvings of the purnaghata kalasha, from which beautiful foliage emerges, an auspicious motif that symbolizes abundance, growth, and prosperity.